When it Rains, Use an Umbrella : Lessons in High-Risk Infrastructure Communications from the Bujagali Hydropower Project - Walsh, Christopher (World Bank, Washington, DC, 2012)
When Uganda's Bujagali Hydropower Project was revived in preparation for a December 2007 Board approval, the World Bank, International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency (MIGA) were faced with a new potential wave of criticism from civil society, the media, and even member governments, in spite of the fact that the project had meticulously followed World Bank Group economic, environmental, and social safeguard policies. This smart lesson describes how active communications, openness, inclusion, and confidence helped address critics of the project and spark the beginning of the end of the East African country's chronic blackouts.